The performance of tool shape on efficiency and quality of forming in incremental sheet-forming process. (2017) - Desai, Bhavin V.; Desai, Keyur P.; Raval, Harit K.
Incremental sheet-forming process is an economical alternative of conventional sheet metal forming process to manufacture parts in small or medium batch size as well as to produce sheet metal prototypes. In the present investigation, to study the effect of tool shape on efficiency and quality of the formed component, two different kinds of tools of same diameter with hemispherical end and spherical end are employed. Forming time is considered as a measure of process efficiency and profile accuracy as a quality of forming. The Taguchi experimental design is applied for experimentation. ANOVA is performed to know the level of significance of the process parameters. It is found that incremental depth step is the most significant process parameter affecting forming efficiency followed by forming speed (feed). Forming speed, wall angle and incremental depth step are the most significant parameters that affect the forming quality.